3D power Doppler in uterine fibroids; influence of gain, cardiac cycle and off-line measurement techniques. (2nd January 2018) - Nieuwenhuis, L. L.; Hehenkamp, W. J. K.; Brölmann, H. A. M.; Huirne, J. A. F.
Abstract: This study answers the question of whether ultrasound machine settings and the cardiac cycle can influence 3D power Doppler (3D PD) indices in the evaluation of uterine fibroid vascularisation. These parameters were reported to affect the vascular indices and cause undesired variation. 3D PD ultrasound was performed using three different gain settings: a fixed predetermined gain (50 dB), a higher gain (65 dB) and an individualised subjectively most optimal gain. Two consecutive 3D PD sweeps were taken to evaluate the effect of the cardiac cycle. A predetermined most optimal fixed gain setting was not different from the individually most optimal chosen gain in vascular assessment of fibroids. A higher gain corresponded with a significantly higher vascular index (VI). Potential variation during the cardiac cycle does not disturb the VI in fibroids.